"Why I Stayed in That Relationship": Barriers to Indigenous Women's Ability to Leave Violent Relationships. (November 2022) - McKinley, Catherine E.; Liddell, Jessica L.
Indigenous women in the United States are among the most vulnerable to intimate partner violence (IPV), which has reached endemic levels. The purpose of this qualitative inquiry was to understand contextual factors and barriers to becoming liberated from violence. Reconstructive analysis of data from a critical ethnography with a sample of 231 women across two tribes who described IPV relationships identified the following themes: controlling relationships, losing sense of priorities, using children, socioeconomic stress, family pressures, and restricting relationships. Results revealed these tactics, which parallel those used in the patriarchal colonialism of historical oppression, impeded women's liberation from relationships.